Editorial. Issue 1 (1st June 2021) - Callan, Brian; Travaglino, Giovanni A.
Abstract : In this first issue of 2021, we find ourselves still in this strange space of a viral pandemic that first emerged in 2019. Yet contentious politics persists in public places, and the present issue reflects Contention' s continued efforts to publish interdisciplinary research-based articles from around the world.